Kebijakan Moneter Berbasis Prinsip Prinsip Islam - Amien Wahyudi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2013)
Islam has its own monetary policy that is different from other economic systems. In terms of objectives, Islam not only emphasizes the equilibrium between the demand and supply of money but also strives for equity with the principles of justice and brotherhood, so as to create a fair distribution of wealth and income as well. In the aspect of management, with the absence of interest, Islam has a big difference with the conventional system, and indirectly, avoid the adverse effects of the interest system. Speculation which is the “Ghost” of the conventional system, the biggest aspect that contributes to the monetary crisis so far, if it does not disappear, can be minimized. The application of profile and loss sharing in financial intermediation can create a more stable economy, because it can minimize the utilization of agregeat money demand for non-essential and non-productive activities, so that efficiency and equitable use of resources can be increased and macroeconomic imbalances that cause inflation can be reduced.